Company law and the interests of company employees - Venter, Willem Mattheus (Department of Commercial Law, 2023)
The present state of law in South Africa appears to create a dichotomy between labour lawyers on the one hand, and commercial lawyers applying their revered company law principles, on the other. This dissertation will deal with some aspects of law which create tension between the two and discuss some solutions towards resolving such tension. The development of the employment relationship makes it imperative to remove from labour law excessive influences of patterns of company law which may exacerbate the relationship between employer and employee. I Some of the difficulties created by company law which manifest themselves in the employment relationship will be examined. This task becomes necessary in order to find some means in the South African labour scene, towards lessening conflict between employers and employees. One needs to search no further than to consider an example such as the impact of sophisticated mergers or take-overs. The application of the legal fiction of the separate entity of a company in these circumstances is perhaps too rigid to inflict upon a relatively unsophisticated .workforce which otherwise enjoys little or no assistance from company law. There is also no touchstone in South African law to guide company directors towards recognising the need for some form of protection of company employees since the. company director is currently bound, in the exercise of his fiduciary duties, to act only in the "interests" of his company. It seems more than likely that South Africa will have a mixed economy . based on market principles for the foreseeable future until constitutional · issues have been laid to rest. The future South Africa is not likely to have a political economy which is either vigorously worker controlled or entirely I free enterprise in character. This may dictate future policy, but the need to be resilient during the period of change, is imperative. This prognosis of the South African labour law scenario makes it extremely difficult to attempt to lay down strict guidelines for dealing with the problems, but a closer examination of the shareholder/ employee positions within a company, the duty of directors, legislation and socio-political trends impacting upon companies, may result in alleviating at least some of the social disorders created by retrenchments. The current situation within the country with its massive unemployment, demands that labour law and its peer, company law, recognise the effect of loss of employment on the wellbeing of workers and that it is inevitable, in instances where tensions are created between these disciplines, that these be addressed to attain urgent conciliation. This may conceivably add to the fiduciary duties of directors of companies by setting mandatory standards which will recognise the severe socio-economic impact of dismissals. It must somehow also be captured within the ambit of the "interests" of a company which the director is obliged by common law to protect. Loss of employment as a result of workforce reductions is widely seen as a major social issue requiring the attention of policy-makers at governmental level as well as that of industry and of undertakings. Lawyers also, must not be seen to be lacking in ability and willingness to create an equitable balance in the modern.day employment relationship. In the last decade, at least, policies applicable to workforce reductions have undergone considerable development in many countries through legislative or administrative action and collective bargaining. It is the purpose of the present study to attempt, through the medium of company law, to address some of these issues with the view to attenuating their dire social results and thereby create a territory on which commercial lawyers and labour lawyers are able to exist in relatively peaceful condominium. This dissertation examines the effect of the company as a legal person and argues for a change in the "interests" of a company from a solely profit making enterprise, to one which, by force of circumstances, must change to keep pace with developments in the employment relationship. This inevitably leads to a discussion of the relationship between the shareholders of a company and its employees and an examination of extended duties of its directors. This becomes necessary if the welfare and interests of a company's employees are to be catered for. Finally, some comment on take-overs, mergers and transfers will be offered and a conclusion, which includes some aspects of juridification, is reached.